Educational Mismatches and Labor Market Impact in Cameroon (Global Journal of Human-Social Science, 2021)
The objective of this study is to capture the effect of educational mismatches on earnings in Cameroon. Based on data from the Fourth Cameroon Household Survey (ECAM IV), this study uses the IV-2SLS estimation method proposed by Wooldridge (2010) to correct for both sample selection and endogeneity issues. At the descriptive level, the results show that 63.3% and 27.6% of graduates are overeducated and horizontally maladjusted, respectively. Also, 45.95% and 19.77% of the workers are respectively in single mismatch (vertical or horizontal mismatch only) and double mismatch. Econometrically, the results reveal that vertical mismatch tends to reduce the wage by 0.39%; horizontal mismatch by 0.4% and double mismatch by 0.41%. We find that, although the difference is small, horizontal mismatch has a more negative impact on earnings in the Cameroon market than vertical mismatch. Moreover, workers with both types of mismatch suffer more from the wage penalty than those with only one form of educational mismatch.
Keywords: educational mismatch; wages; cameroon